Analisis Makna Kata Hana dan Bunga Sebagai Polisemi (Kajian Linguistik Kognitif) - Rosalina Wahyu Riani (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2019)
Cognitive linguistics views that the meaning of a word, especially in polysemi, doesnot just appear, but there is something that motivates and lies behind it. To describethe relationship between meanings in polysemy can be done through language style.Categorization and comparing activities can occur in the form of metaphorical, metonymy,and synchronic forms. The word 'ﬂower' in Indonesian with ana hana ’in Japanese hasalmost the same meaning and function. This study aims to determine the meaning of theword ﬂower and hana seen from the perspective of cognitive linguistics. This study usesa qualitative descriptive method by taking data from various sources. The results of thisstudy are 1) in general the meaning of the word "ﬂower" is something beautiful, calmingthe heart, pleasing to the eye, pleasant to hear, fragrant smell; 2) in general the meaningof the word "hana" is a beautiful woman; Wreaths; ﬂower picture card game; colorful,striking, brilliant, beautiful.Keywords: cognitive linguistics, polisemi, hana, bunga